Building Smart Tourism: Exploring the Potential of Tourism Apps for Branding - Serlina, Andi; Lutfi, Muhammad; Baharuddin, Baharuddin (Jurnal Studi Ilmu Pemerintahan, 2024)
This research comprehensively studies the impact of the "Ayo ke Sinjai" app on smart branding in Sinjai Regency. Using a qualitative research approach, this study conducted an in-depth analysis through literature reviews, online media portals, and rarely explored journals. The resulting findings demonstrate the tremendous tourism potential inherent in Sinjai Regency. As a strategic move to showcase this potential, the Sinjai Regency government launched the "Ayo ke Sinjai" application to ease tourists' access to information regarding various exciting tourist attractions. Despite the promising potential of this application, its implementation faces challenges, especially in terms of user accessibility due to persistent technical errors. This interferes with the smooth dissemination of vital information to potential tourists, thereby reducing the expected benefits of the app. This study highlights the many tourism riches waiting to be explored in Sinjai Regency and underscores the importance of resolving technical issues for the "Ayo ke Sinjai" app. A functional and easy-to-use platform is essential to drive smart branding effectively so that tourists can easily explore and appreciate the various tourist attractions in the area.